2011
DOI: 10.1124/mol.110.070540
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Family of Insect-Selective Peptide Neurotoxins Targeting Insect Large-Conductance Calcium-Activated K+ Channels Isolated from the Venom of the Theraphosid Spider Eucratoscelus constrictus

Abstract: Spider venoms are actively being investigated as sources of novel insecticidal agents for biopesticide engineering. After screening 37 theraphosid spider venoms, a family of three new "short-loop" inhibitory cystine knot insecticidal toxins (-TRTXEc2a, -TRTX-Ec2b, and -TRTX-Ec2c) were isolated and characterized from the venom of the African tarantula Eucratoscelus constrictus. Whole-cell patch-clamp recordings from cockroach dorsal unpaired median neurons revealed that, despite significant sequence homology wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 38 publications
2
22
0
2
Order By: Relevance
“…Previous studies have identified peptide toxins that modulate BK channels from venoms of various animals including scorpion (28 -30), cone snail (31), snake (32), bee (33), and spider (34). Among these toxins, charybdotoxin (ChTx) and iberiotoxin (IbTx) have been intensively studied for molecular pharmacology and used as an effective tool to identify BK channels in various tissues that contributed greatly in the understanding (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified peptide toxins that modulate BK channels from venoms of various animals including scorpion (28 -30), cone snail (31), snake (32), bee (33), and spider (34). Among these toxins, charybdotoxin (ChTx) and iberiotoxin (IbTx) have been intensively studied for molecular pharmacology and used as an effective tool to identify BK channels in various tissues that contributed greatly in the understanding (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus: I BK(Ca) control = protocol 1 -protocol 3; while I BK(Ca) toxin = protocol 2 -protocol 3. 1 mM CdCl 2 and 5 mM 4-AP were included in the external solutions to block Ca V channel currents and I K(A) , respectively (Grolleau and Lapied, 1995;Gunning et al, 2008;Windley et al, 2011). Test pulses to +30 mV for 100 ms from a holding potential (V h ) -80 mV delivered at 0.1 Hz were used to evoke outward non-inactivating K DR and K Ca 1.1 channel currents.…”
Section: Voltage-gated Ion Channel Electrophysiologymentioning
confidence: 99%
“…Consequently, K Ca 1.1 channel current isolation was achieved using the following procedure (Gunning et al, 2008;Windley et al, 2011). Initially, both I K(DR) and I K(Ca) were recorded concurrently (protocol 1).…”
Section: Voltage-gated Ion Channel Electrophysiologymentioning
confidence: 99%
See 2 more Smart Citations